A amizade e a alter-direcionalidade do desejo em Aristóteles - Faustino, Lucas Rocha (2019)
In this thesis, we are opposed to the interpretations that understand that Aristotle's practical philosophy represents a model of rational egoism. For the Aristotelian agent, insofar as he is involved in satisfying the defining criteria of eudaimonia, would be a kind of collector gathering the means and instruments relevant to his self-realization – the ultimate end of his particular desire. From this understanding, we would have, consequently, the impossibility of establishing the alterity of the other individuals with whom we act, since these individuals, to the agent, would have only instrumental value and never a value in themselves. We argue, therefore, that this way of reading Aristotle's practical philosophy is unsustainable and contradictory when we seriously consider the propositions established on his theory of friendship and correlate them with the "eudaimonist axiom." Our aim is to point out elements within the Aristotelian writings, which reveal that friendship bases a relationship that subordinates any instrumentalizer primacy for the relations between men. For what is in fact at stake is not only the "ego-directed" desires of each agent, but the construction of a basis of action and political-ethical "co-relation" in which the fundamental is what is common among us, what we "share" and "feel" with others while others by themselves. For this reason, it is fundamental to understand that in friendship Aristotle bases the possibility of "alter-directed" desires, through the criterion of benevolence, as well as inaugurates the possibility of deliberate choice for a specifically human conviviality, something that only exists when men freely choose to live with other men qua men for themselves.